Developing the framework for Halal friendly tourism in Malaysia - Wan Zulkifli, Wan Sahida; Ab Rahman, Suhaimi; Awang, Khairil Wahidin; Che Man, Yaakob (Medwell Online, 2011)
Tourism is a sector that has been identified by government as a catalyst for the economy. In this context, Islamic tourism has been chosen as the key focus areas where it is considered to attract Muslim tourists. Halal industry has becoming a lucrative market globally either for products or services. However, the services sector such as tourism has yet to tap into this lucrative market even though the Halal travel is gaining popularity globally. Basically, Halal tourism is relatively a new concept that is gaining high demand, especially from Halal conscious traveler. However, the issue arises when there is no framework for Halal friendly tourism has been developed in Malaysia. In this discussion, the researcher has proposed a conceptual framework for Halal friendly tourism activities. From the proposed framework hopefully that one day, the standard framework of Halal friendly tourism could be established and practiced in future.